PENGEMBANGAN MEDIA DIORAMA PADA PEMBELAJARAN METAMORFOSIS HEWAN DI KELAS IV SDS PEMBANGUNAN TANJUNG MORAWA T.A 2022-2023 - Fahlevi Ariani; Sukmawarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this research is to develop three-dimensional diorama media that is feasible and practical to use after being validated by several experts and response tests by students and teachers. The research method uses the ADDIE development model. The instruments used were media feasibility test questionnaires and student and teacher response questionnaires. The research subjects were 2 UMN Al-Washliyah lecturers consisting of 1 material expert validation and 1 media expert validation and 2 class IV teachers and 9 class IV students. The developed three-dimensional diorama media was assessed by experts with a percentage of 90% (material experts) 100% (media experts) with a very decent category. Student response tests were carried out on 21 grade IV students at SDS Pembangunan Tanjung Morawa with a percentage of 93.4% (strongly agree category). And the trial of 2 class IV teacher responses with a percentage of 93.3% (strongly agree). Very decent category and totally agree. Based on the results of the feasibility and practicality tests, the three-dimensional diorama media was declared feasible as a learning medium at SDS Pembangunan Tanjung Morawa